Implementasi Total Quality Managemen di SMPIT Abu Bakar Yogyakarta dan Implikasinya Terhadap Prestasi Sekolah - Akhsanul Fuadi (LITERASI (Jurnal Ilmu Pendidikan), 2020)
Implementation of Total Quality Management is absolutely necessary to be implemented in school to increase schools achievement . Total Quality Management is implemented by SMPIT Abu Bakar Yogyakarta as a strategy to increase a progressive achievements at the SMPIT Abu Bakar Yogyakarta. This management is implemented to every aspects to realize the progressive achievements and never stop.The results of the implementation of the "Total Quality Management" strategy at SMPIT Abu Bakar Yogyakarta proved to be able to improve the achievements and quality of education at SMPIT Abu Bakar Yogyakarta. Based on the data starting from the 2010/2011 school year, Abu Bakar SMPIT won more than 200 championships by the students from the regency level to the national level. There was even one international event (ASEAN). There were 10 championships won by teachers from the regency level to the National level. For institutions, the school received an award as a school with national level integrity, a national family education model school, a superior quality model school at the provincial level, a champion of an environmentally friendly school for boarding program